Maternal nutrition and its intergenerational links to non-communicable disease metabolic risk factors: a systematic review and narrative synthesis - Elizabeth Wilkins; Kremlin Wickramasinghe; Jessie Pullar; Alessandro R. Demaio; Nia Roberts; Karla-Maria; Katharine Noonan; Nick Townsend (BMC, 2021)
Abstract Background Non-communicable diseases (NCDs) are the leading cause of death and disability globally, while malnutrition presents a major global burden. An increasing body of evidence suggests that poor maternal nutrition is related to the development of NCDs and their risk factors in adult offspring. However, there has been no systematic evaluation of this evidence. Methods We searched eight electronic databases and reference lists for primary research published between 1 January 1996 and 31 May 2016 for studies presenting data on various dimensions of maternal nutritional status (including maternal exposure to famine, maternal gestational weight gain (GWG), maternal weight and/or body mass index (BMI), and maternal dietary intake) during pregnancy or lactation, and measures of at least one of three NCD metabolic risk factors (blood pressure, blood lipids and blood glucose) in the study population of offspring aged 18 years or over. Owing to high heterogeneity across exposures and outcomes, we employed a narrative approach for data synthesis (PROSPERO= CRD42016039244, CRD42016039247). Results Twenty-seven studies from 10 countries with 62,607 participants in total met our inclusion criteria. The review revealed considerable heterogeneity in findings across studies. There was evidence of a link between maternal exposure to famine during pregnancy with adverse blood pressure, blood lipid, and glucose metabolism outcomes in adult offspring in some contexts, with some tentative support for an influence of adult offspring adiposity in this relationship. However, the evidence base for maternal BMI, GWG, and dietary intake of specific nutrients during pregnancy was more limited and revealed no consistent support for a link between these exposures and adult offspring NCD metabolic risk factors. Conclusion The links identified between maternal exposure to famine and offspring NCD risk factors in some contexts, and the tentative support for the role of adult offspring adiposity in influencing this relationship, suggest the need for increased collaboration between maternal nutrition and NCD sectors. However, in view of the current scant evidence base for other aspects of maternal nutrition, and the overall heterogeneity of findings, ongoing monitoring and evaluation using large prospective studies and linked data sets is a major priority.